Development of Prasman Leaf Suspension in Combination With Pulvis Gummi Arabici and Hydroxyethylcellulose Using Simplex Lattice Design Method - Dina Salwa Atiqi; Slamet Slamet; Wirasti Wirasti; Dwi Bagus Pambudi (Universitas Muhammadiyah Surakarta, 2022)
Suspending agents affect the viscosity, storage, and re-dispersal of suspension preparations. This study aims to optimize the combination of suspending agent PGA and hydroxyethylcellulose to obtain the optimum suspension preparation. This suspension formulation uses a computer program design expert version 11 using the Simplex Lattice Design (SLD) method with 2 suspending agents, namely PGA and hydroxyethylcellulose. This SLD method produces 8 formulas. The parameters of these eight formulas were measured including their physical properties, such as organoleptic, pH, viscosity, sedimentation volume, and redispersibility of the preparation. Data were analyzed and produced a graphic equation of each response that gave the optimum suspension formulation. The formula I showed optimal parameters, i.e. physical stability, organoleptic stability, the pH of 5, the viscosity value of 59 cP, 0.04 mL sedimentation, and 95% redispersibility value with the concentration of the suspending agent is 6.25% of PGA and 0.775% of hydroxyethylcellulose, and the desirability value of 0.57. The results indicated that the suspension preparation had the characteristics of low viscosity, the particles settle quickly and are easily re-dispersed. Analysis of ANOVA statistical data on viscosity, sedimentation volume, and redispersibility of suspension preparations showed a p-value 5 or significant meaning that the use of the SLD method affected increasing and decreasing the response value.